FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA GURU: LITERATURE REVIEW - Hidayatulloh; Mumtaz, Shafira; Rindanigsih, Ida (Academic Journal Research, 2023)
This study aims to obtain a theoretical basis that can support solving the problem being studied on the effect of motivation and work stress on teacher performance. The theory obtainer is the first step so that researchers can better understand the problemed being researched correctly according to a scientific framework. The method used in this research is a literature review. Researchers select the feasibility of research articles based on the background of the article, research methods, discussed results, discussion and conclusions. In this study, the data source used is secondary data sources. An article search was carried out via the lens.org website to conduct a literature search with the keywords "motivation" "stress" and "teacher performance" in the range of 2020 to 2023. As a result, there were 61 article findings. Then the researcher used the keyword "work motivation" there were 10,386 articles. Then the keyword "work stress" has 2,498 articles. And the keyword "teacher performance" contains 5,206 articles. The next step, analyzing the Literature Review method on five articles that match the keywords. The results obtained, namely, the variables of motivation and stress have a positive and significant effect on teacher performance directly. This is based on previous research findings in several educational institutions in Indonesia. Teacher performance is influenced by motivation and work stress. Variables of motivation and work stress cannot act independently. Reviewing the research that has been done, the findings obtained regarding the description of the influence of motivation and work stress on teachers in Indonesia are considered not to be able to walk alone. Many other factors affect the level of teacher performance in educational institutions. Such as job satisfaction, teacher compensation, teacher competence, principal leadership, discipline, work environment, teacher productivity, awards, organizational culture, and many more.